Clinicopathological Features of Lupus Nephritis Patients in North-East India; A Single Center Retrospective Observational Study (Journal of Renal and Hepatic Disorders, 2021)
Clinicopathological presentation of lupus nephritis (LN) patients varies with different race and ethinicity of the population. Only few studies describe clinicopathological spectrum of LN patients in the Indian population. The aim of this study was to determine the clinicopathological spectrum of LN in the North-East Indian population. This was a retrospective observational study that included patients with LN at a tertiary care center in North-East India from March 2007 to August 2018. Clinical and histopathological data at the time of presentation were collected from hospital records. Renal biopsies were examined by light microscopy and direct immunofluorescence techniques. A total of 340 patients of LN were included in this study. The mean age of presentation was 22.42 ± 4.3 years. The minimum age at presentation was 8 years and 18.8% belonged to the
Keywords: clinicopathological presentation; histopathology; lupus nephritis; systemic lupus erythematosus